LENGTH OF STAY DI INSTALASI GAWAT DARURAT SEBAGAI INDIKATOR MUTU PELAYANAN KESEHATAN DI RUMAH SAKIT X TAHUN 2024 - Dwisari, Gustiane Adriani; Sari, Kurnia (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2024)
The Emergency Department (ED) is crucial for ensuring patient care and safety in hospitals. A key performance indicator is Length of Stay (LOS), where prolonged LOS can lead to overcrowding, increase the risk of adverse events, and lower patient satisfaction. This study examines the service flow, barriers, and root causes of LOS in Hospital X's ED and provides improvement recommendations. Data were gathered through observation of 30 patients, interviews, and document reviews. Lean Thinking principles and the BAS method from BASICS (Baseline, Assess, Suggest Solution, Implement, Check Result, Sustain) were used in the analysis, employing flowcharts to map the process, Value Stream Mapping to identify waste, and The Five Whys to analyze root causes. Results show that 65.5% of time was spent on non-value-added activities, 23.4% on necessary but non-value-added, and 11.1% on value-added activities, with a total Lead Time of 7 hours, 55 minutes, and 29 seconds. Patient-side waste includes waiting (94.9%) and transportation (5.1%). Bottlenecks were found in waiting for inpatient registration (25.2%), waiting for the primary physician's advice (22.9%), waiting for diagnostic results (22.3%), and waiting for inpatient readiness (18.2%), totaling 88.6%. LOS improvement can be achieved through lean tools such as standardized work, visual management, heijunka, kaizen, and just-in-time.